RESEARCH IN ANTARCTICA, AN UNFORGETTABLE EXPERIENCE OF A LIFETIME – DR. FOONG SWEE YEOK - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 18 February 2016 – There was a deep feeling of gratefulness and excitement shared by the researchers upon arriving on Malaysian soil, on the evening of Sunday, 14 January 2016 and among them was the lecturer from the School of Biological Sciences Universiti Sains Malaysia (USM), Dr. Foong Swee Yeok, 44.